Of the observation models in the General Theory of Cost (Costos y Gestión, 2020)
To manage organizations and solve the particular problems that arise from reality, the technique mustprovide the tools, but it is also necessary to have the basic theoretical principles and postulates that providesupport to costing techniques. In this sense, the General Cost Theory (TGC) tries to provide a logical structureto analyze and study a particular economic phenomenon: costs.It is important to emphasize that the theories support or use different observational models to facilitate thestudy and description of the problem under analysis. Consequently, it is necessary to advance in the studyand establishment of the different Models used in the General Theory of Cost that help to adequately analyzethe object of study.The objective of this work is to carry out a reflexive analysis on the processes of accumulation of costs,relying on the rules of a technical-organizational nature that preside over the progress of the productiveprocesses, in order to make a proposal about the study of the cost observation models. To achieve this goal,an interpretative analysis of texts and research papers written by recognized authors in the discipline wascarried out.
Keywords: Cost; Theory; Management